The Effectiveness of Using Tiktok in Learning Pronounciation Subjects in the English Language Education Study Program, Wiralodra University, Indramayu - Ela Meiliasari; Lisa Paramitha Lorentza; Mia Yasna Ratimaya; Ahmad Khotibul Umam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
TikTok is a social media platform that allows users to create short videos accompanied by a variety of feature options. This application is widely used by young people to obtain information, knowledge, and entertainment. The purpose of this study was to determine the effectiveness of the TikTok application which is used as a medium for learning pronunciation in English. This research was carried out at a private University in Indramayu with fiveteen undergraduate students from the second year of the English Education Department as participants in this research. This study uses qualitative methods which are included in field research with data collection techniques using observation, questionnaires with a Likert scale, and interviews. After research, the results of the study show that the use of TikTok can package pronunciation learning in an interesting way. It can be concluded that the Tiktok application is effective for learning pronunciation in English.